Предмет: Алгебра, автор: NastiaNastia06

Help (6с-4)^2-(4с+3)^2=0

Ответы

Автор ответа: 5555566666777777
1

Ответ:

(6c - 4)² - (4c + 3)² = 0

(6c - 4 - (4c + 3))(6c - 4 + (4c + 3)) = 0

(6c - 4 - 4c - 3)(6c - 4 + 4c + 3) = 0

(2c - 7)(10c - 1) = 0

1) 2c - 7 = 0

2c = 7

c = 7/2 = 3,5

2) 10c - 1 = 0

10c = 1

c = 1/10 = 0,1

Ответ: 0,1 ; 3,5

Объяснение:


NastiaNastia06: Спасибо ❤️
Автор ответа: vikasmir010
1

Объяснение:

Применяется формула сокращённого умножения: разность квадратов

Приложения:
Похожие вопросы